Assessing the factors influencing the adoption of geothermal energy to support the national grid in emerging economies: Implications for sustainability - Md. Fahim Bin Alam; Saifur Rahman Tushar; Binoy Debnath; Amirhossein Taghipour; Hasan Dınçer; Abu Reza Md. Towfiqul Islam; A.B.M. Mainul Bari; Sadman Sakib Tushan (Sustainable Operations and Computers, 2024)
The ongoing Russia-Ukraine conflict has made the global energy crisis a severe issue, particularly for emerging economies with a sharp rise in load shedding in communities, disruptions in industrial operation, and an increased cost of living. Shifting our focus from fossil fuel-based energy to sustainable and promising renewable energy sources, like geothermal energy (GE), is crucial to addressing the ongoing energy crisis. Therefore, this study aims to evaluate the significant factors influencing the adoption of GE to support the national grid of an emerging economy like Bangladesh. An integrated framework consisting of the Delphi method, fuzzy total interpretive structural modeling (TISM), and fuzzy Cross-Impact Matrix Multiplication Applied to Classification (MICMAC) analysis was utilized in this study to evaluate the hierarchical interrelationships among the significant factors. The findings indicate that the top two influencing factors are the “scope for new investments and employment” and the “growing need for inexpensive and renewable energy sources”. The study's findings can offer significant insights to decision-makers and policymakers, which can aid in the development of long-term strategic plans to facilitate the successful adoption and integration of GE and promote sustainability and low-carbon economy in the energy sector.
Keywords: Social Acceptance of Renewable Energy; Delphi Technique in Research; Integrated Energy Systems Optimization